Braille-CM-TUI: ambiente de apoio à construção de conhecimento via mapas conceituais por estudantes com cegueira - Beal, Franciele (2020)
A growing phenomenon has caused negative consequences on blind education. This is the ”desbrailização” (the process of braille disuse) that consists of replacing the braille system with audio technologies such as the spoken book and digitized texts that can be heard using speech synthesizers. Many blind people no longer want to read braille. With audio technologies, the blind person has access to any text type, and it is easier to hear than to read in braille. Also, many blind people say that braille is not part of the daily life of visionary people and with audio technologies, they can be included in regular schools more easily. In this situation, many blind people no longer want to read braille, leaving aside their writing and reading system, which, for students of braille literacy, determines a significant limitation in their citizenship enjoyment. On the other hand, techniques such as concept maps are not taught to the blind because they are considered not accessible to them. In this context, a tangible user environment has been proposed for students with blindness to build concept maps using braille, the Braille-CM-TUI, in an attempt to combat the braille disuse. This environment has a tangible interface with braille elements for the construction of concept maps and an authoring tool for the teacher to create didactic sequences of concept map activities. The environment was developed based on a literature review and was subsequently taken to two schools for its evaluation and improvement by specialized teachers and students with blindness, through an action research process. Blind students participated in a workshop to learn the concept of concept maps. Two specialized teachers received training on concept maps and remotely evaluated Braille-CM-TUI. The empirical evaluation method was used to collect qualitative data. The results of the workshop showed that blind students were able to appropriate and make use of concept maps. The results of the remote assessments carried out by the teachers, obtained from observation and opinion collection, showed a positive assessment for Braille-CM-TUI and the authoring tool. Improvement possibilities have been identified that will be implemented in future works.